Tongues of Flame - Brown, Mary Ward (Book collections on Project MUSE., 1753)
These beautifully crafted stories depict the changing relationships between black and white southerners, the impact of the civil rights movement, and the emergence of the New South. Mary Ward Brown is a storyteller in the tradition of such powerful 20th-century writers as William Faulkner, Harper Lee, Flannery O'Connor, and Eudora Welty-writers who have explored and dramatized the tension between the inherited social structure of the South and its contemporary dissolution. With Tongues of Flame, her first collection of short stories, Brown bares the awkward, som.